Temporal regulation of genetic programs governing multiple cell death during myocardial ischemia-reperfusion injury - Pang, Qiuyu; Meng, Xiangmin; Zhou, Zhenfang; You, Lu; Yuan, Jinghan; Feng, Qipu; Zhu, Bingmei (Frontiers in Genetics, 2025)
IntroductionReperfusion serves as an effective therapeutic strategy for myocardial infarction (MI), but it causes damage to the heart. Although many studies have investigated the mechanism of disparate forms of cell death in myocardial ischemia-reperfusion injury (I/R), there remains a paucity of studies focus on the direct comparison of the mode of cell death events resulting from different reperfusion periods.MethodsWe conducted an analysis of different sequencing data available in public databases to investigate the relationship between the diverse patterns of cell death and different reperfusion times. Additionally, we evaluated the time window of multiple categories of cell death between cells and mice.ResultsWe explored the relationship between the various modes of cell death and different reperfusion times induced by 6h, 12h and 24 h reperfusion. Our findings revealed that apoptosis occurred in the early stage of I/R injury and continued to appear as the reperfusion time increased. Meanwhile, the changes in autophagy and cuproptosis were also more obvious in the early stage of reperfusion. Notably, ferroptosis and necrosis emerged as the predominant forms of cell death during the medium-to-long-term reperfusion period.DiscussionIn summary, this study demonstrates that apoptosis takes place during the early stage of reperfusion. Besides, ferroptosis, necrosis and pyroptosis played a crucial role in the prolonged I/R injury period.